Changes to the daily pattern of methadone-related deaths in England and Wales, 1993-2003. - Morgan, O; Johnson, H; Rooney, C; Seagroatt, V; Griffiths, C (2006)
Previous studies suggest that fatal poisoning deaths involving methadone occur more frequently on the weekends. We assessed changes in the daily pattern of mortality because of methadone poisoning following a review of drug misuse services in 1996 and publication of revised clinical guidelines in 1999. We also compared this to the daily pattern of deaths involving heroin/morphine. The Office for National Statistics provided data on all deaths in England and Wales between 1993 and 2003 for which methadone and heroin/morphine were mentioned on the coroner's certificate of death registration after inquest, with or without alcohol or other drugs. There were 3098 deaths involving methadone. The death rate increased up to 1997 and then declined. Initially, there was a marked excess of deaths occurring on Saturdays. The rate of decline was greatest for deaths occurring on Saturdays. As a result, the Saturday peak disappeared (P = 0.006). There were 6328 deaths involving heroin/morphine. No change in the daily pattern of heroin/morphine deaths was observed during the study period. Although the marked change in the epidemiology of methadone deaths coincided with recommendations for service redevelopment and clinical management of methadone treatment, the contribution of improved prescribing practice or treatment services is unclear.